Attitude and Perception of Farmers Towards e-Learning (Indian Journal of Extension Education, 2013)
e-Learning is a new concept to our agricultural system,where most of the farming communities have low access to the right information sources. It can contribute a lot through the provision of apt learning situation to officials, agriculture students as well as farmers and will dramatically improve agricultural education by allowing greater access to information. The study was undertaken in the Malappuram district of Kerala state to determine the attitude and perception of farmers towards e-learning. A group of sixty e-learners and sixty non e-learners was selected randomly to obtain significant information. It was found out that although the benefits of e-learning are many like easy access to information, time and cost effective, flexible; even then non e- learners had a negative attitude and unfavorable perception index towards e- learning.